2004
DOI: 10.1080/01612840490443473
|View full text |Cite
|
Sign up to set email alerts
|

Restriction and Control: The Perceptions of Mental Health Nurses in a UK Acute Inpatient Setting

Abstract: In the United Kingdom there has been growing unease over standards of care and treatment in acute inpatient psychiatric services. Although recent reforms have declared nurses as pivotal to the social transformation required, few accounts inform modernisers about the reality of social systems, relations, and events in modern acute psychiatric services. This qualitative study explores the situation of nurses working in acute inpatient psychiatric services. It particularly describes the social control elements th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 23 publications
1
59
0
1
Order By: Relevance
“…Some of the effective interventions targeting restraint reduction incorporated measures to transform the unit culture in relation to this restrictive way to control aggressive behavior (Taxis, 2002;Visalli et al, 1997). Psychiatric units have their own culture, with social control practices strongly embedded in shared norms and values (Hall, 2004;Johnson, 1998). To guide future inquiry into this important yet largely neglected phenomenon, organizational culture will be added to the organization of nursing care components of the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the effective interventions targeting restraint reduction incorporated measures to transform the unit culture in relation to this restrictive way to control aggressive behavior (Taxis, 2002;Visalli et al, 1997). Psychiatric units have their own culture, with social control practices strongly embedded in shared norms and values (Hall, 2004;Johnson, 1998). To guide future inquiry into this important yet largely neglected phenomenon, organizational culture will be added to the organization of nursing care components of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Other nurses reported that job satisfaction results from having control over decision making (Farrell & Dares, 1999). Psychiatric nurses in England described their work as dominated by social control functions, limiting their authority to change their own working practices (Hall, 2004). Although job satisfaction and stress were not measured in this study, the nurses reported that they experienced failures in control, effectiveness, and humanism.…”
Section: Nurse Practice Environmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Le traitement infligé aux personnes en institution est également une source majeure de critiques pour plusieurs auteurs (Hall, 2004 (Winick, 2008). Ceci démontre la contradiction entre la personne et l'État tel que décrit par Szasz (2007) : en agissant contre la liberté individuelle, l'État est un dispositif de coercition qui détient le monopole de l'usage légal de la violence.…”
Section: Chapitre II Recension Des éCrits Et Cadre Théoriqueunclassified
“…She found that staff were socialised into the need for physical restraint and seclusion as the means for ensuring control; staff who favoured or tried 'verbal therapeutic interventions' would be isolated and unsupported by their colleagues. Themes of restriction, surveillance and control were also central to a content analysis of mental health nurses' perceptions of their work by Hall (2004) with some participants believing such functions made a positive contribution to care, and others certain that they disrupted or precluded engagement in nurse patient relationships.…”
Section: Staff Experiencementioning
confidence: 99%